Advanced strength and conditioning an evidence-based approach - Comfort, Paul; Turner, Anthony (Anthony N.) (Routledge,Taylor & Francis Group, 2018)
Becoming an effective strength and conditioning practitioner requires the development of a professional skills set and a thorough understanding of the scientific basis of best practice. Aimed at advanced students and beginning practitioners, this book explores the latest scientific evidence and applied it to exercise selection and programming choices across the full range of functional areas in strength and conditioning, from strength to power to speed and agility. With coverage of data analysis and performance feedback, both vital skills for contemporary strength and conditioning coach, this concise but sophisticated textbook is the perfect bridge from introductory study to effective professional practice. Written by experts with experience in a wide variety of sports, its chapters are enhanced by extensive illustrations and address key topics such as: fitness testing and data analysis; developing strength and power; motor skill acquisition and development; strategies for competition priming; monitoring training load, fatigue and recovery. Advanced Strength and Conditioning: an evidence-based approach is a valuable resource for all advanced students and practitioners of strength and conditioning and fitness training